Impact assessment of sunflower in Zimbabwe - Murata, M.; Anandajayasekeram, P.; Mudhara, M.; Martella, D.; Mazhangara, E.P. (CAB International, 2007)
The objective of this study was to assess the impact of sunflower research, extension and the enabling environment in Zimbabwe from 1976 to 2000. The study concentrated on comparing the social costs and returns of the sunflower R&1) investment. Both primary and secondary data were used in the analysis. Using a standard questionnaire and multistage sampling, information was collected from communal and commercial farmers in Natural Regions 11, 111 and IV_ Results of the survey indicate that sunflower is a universally adopted crop in the communal areas across all three natural regions, and the area under sunflower cultivation has increased substantially over the years. However, communal area farmers' adoption of improved varieties and better management practices is low. The study points out the need for research to explore the constraints on the adoption of improved varieties and improved agronomic practices. One of the weaknesses of the R&D programme on sunflower has been the limited release of improved varieties. The study estimated the rate of return (ROR) to be 12% for sunflower R&D in Zimbabwe over the period 1976-2000. A sensitivity analysis of the estimated ROR indicated that ROR is sensitive to changes in research costs. The net environmental effect of sunflower R&D was difficult to assess, in the absence of biophysical data to conduct a systematic analysis. The crop, however, was found to have a positive impact on food security, as it is grown successfully in marginal environments, and the income generated is used to meet the daily needs of the households. The results of this study clearly indicate that the ROR on past investments in sunflower R&D in Zimbabwe is attractive enough to warrant continued investment.